Graphene Oxide-Linezolid Combination as Potential New Anti-Tuberculosis Treatment - Flavio De Maio; Valentina Palmieri; Giulia Santarelli; Giordano Perini; Alessandro Salustri; Ivana Palucci; Michela Sali; Jacopo Gervasoni; Aniello Primiano; Gabriele Ciasca; Maurizio Sanguinetti; Marco De Spirito; et al. (Nanomaterials, 2020)
Global pandemic management represents a serious issue for health systems. In some cases, repurposing of existing medications might help find compounds that have the unexpected potential to combat microorganisms. In the same way, changing cell–drug interaction by nanotechnology could represent an innovative strategy to fight infectious diseases. Tuberculosis (TB) remains one of the most alarming worldwide infectious diseases and there is an urgent need for new drugs and treatments, particularly for the emergence and spread of drug-resistant Mycobacterium tuberculosis (Mtb) strains. New nanotechnologies based on carbon nanomaterials are now being considered to improve anti-TB treatments, and graphene oxide (GO) showed interesting properties as an anti-TB drug. GO, which preferentially accumulates in the lungs and is degraded by macrophagic peroxidases, can trap Mycobacterium smegmatis and Mtb in a dose-dependent manner, reducing the entry of bacilli into macrophages. In this paper, combinations of isoniazid (INH), amikacin (AMK) and linezolid (LZD) and GO anti-mycobacterial properties were evaluated against Mtb H37Rv by using a checkerboard assay or an in vitro infection model. Different GO effects have been observed when incubated with INH, AMK or LZD. Whereas the INH and AMK anti-mycobacterial activities were blocked by GO co-administration, the LZD bactericidal effect increased in combination with GO. GO-LZD significantly reduced extracellular mycobacteria during infection and was able to kill internalized bacilli. GO-LZD co-administration is potentially a new promising anti-TB treatment at the forefront in fighting emerging antibiotic-resistant Mtb strains where LZD administration is suggested. This innovative pharmacological approach may lead to reduced treatment periods and decreased adverse effects. More importantly, we demonstrate how nanomaterials–drugs combinations can represent a possible strategy to quickly design drugs for pandemics treatment.